Exit-Site Infection: A Comparison of Classification Systems. Issue 6 (November 2018) - Sangeetha, B.; Deepa, N.; Hemalatha, M.; Latha, C.M.; Ram, R.; Kumar, V. Siva
In general, in peritoneal dialysis (PD) practice in hospitals, Twardowski and Prowant's exit-site classification system is used, while the International Society for Peritoneal Dialysis (ISPD) exit-site scoring system is practical to use in community visits with less experienced healthcare personnel. Nevertheless, when exit-site scoring is 3 points under the ISPD exit-site score system and it falls in the category of equivocal under the Twardowski and Prowant's exit-site classification, the physician should be vigilant about the possibility of developing peritonitis, and hence, patients need to be kept under periodic monitoring.